Labio y paladar fisurado asociados a la función fonética del aparato estomatognático. - Montesdeoca Morales, Anahí de los Ángeles (2024)
Cleft lip and palate, also known as cleft lip and palate, are a set of congenital malformations of the craniofacial complex. The objective of the research was to analyze cleft lip and palate associated with the function of phonation. A review was carried out that included articles from the last ten years that met the selection criteria found in scientific databases such as PubMed, SciELO, Scopus, and Google Scholar. A total of 35 articles were obtained that met the selection criteria. As a result, it was determined that the phonemes /p/, /k/, and /t/ were the most affected. As infants develop, so does their velopharyngeal competence. Most patients presented mild nasality, and early surgical interventions were more effective in treating this pathology. It was concluded that knowledge in theory and clinical practice allows for adequate and complete multidisciplinary management focused on improving the quality of life of those affected.